2020
DOI: 10.1186/s41983-020-00184-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficiency between platelet rich plasma and corticosteroid injection therapies in patients with Carpal tunnel syndrome: a prospective randomized controlled study

Abstract: Background: Carpal tunnel syndrome (CTS) is the most common upper limb entrapment neuropathy caused by compression of the median nerve as it traverses the wrist at the carpal tunnel. Objectives: To compare the effect of single dose of platelet-rich plasma (PRP) injected locally with that of corticosteroid in patients with CTS. Subjects and methods: A total of 60 patients with very mild to moderate unilateral CTS were recruited to the study. PRP was prepared via two centrifugation procedures. The patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 45 publications
1
27
2
Order By: Relevance
“…When Uzun et al's study [ 13 ] was removed, BCTQs at 3rd-month follow-up was P < 0.00001, I 2 = 1% without additional heterogeneity. Similarly, there was no heterogeneity in DML after removing Hashim et al's study [ 30 ] ( P = 0.91, I 2 = 0%). Besides, the results did not show substantive difference compared to the original analysis in remaining indicators.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…When Uzun et al's study [ 13 ] was removed, BCTQs at 3rd-month follow-up was P < 0.00001, I 2 = 1% without additional heterogeneity. Similarly, there was no heterogeneity in DML after removing Hashim et al's study [ 30 ] ( P = 0.91, I 2 = 0%). Besides, the results did not show substantive difference compared to the original analysis in remaining indicators.…”
Section: Resultsmentioning
confidence: 74%
“…All studies compared clinical outcomes of PRP injection versus other conservative treatments for management of mild to moderate CTS. Besides, control groups comprised corticosteroid injection in 5 trials [ 13 , 27 30 ], saline injection in 1 trial [ 31 ], and a splint in 3 trials [ 32 34 ]. Of the 9 included studies, 7 studies were considered to have a low risk of bias, while the 2 remaining studies were found to have a high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through reading the full text, fifteen records were excluded because of irrelevant to our topics, no relevant data and ongoing clinical research that has not yet been published. Finally, eight RCTs ( Wu et al, 2017 ; Malahias et al, 2018 ; Raeissadat et al, 2018 ; Senna et al, 2019 ; Shen et al, 2019 ; Eltabl et al, 2020 ; Hashim et al, 2020 ; Chen et al, 2021b ), including 436 participants, met the selection criteria and were included in this meta-analysis. The flow diagram involved in the current study is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics and preparations of PRP injection among the eight included RCTs are shown in Tables 1 , 2 . In these enrolled studies, three studies were conducted in Egypt ( Senna et al, 2019 ; Eltabl et al, 2020 ; Hashim et al, 2020 ), and three studies in China ( Wu et al, 2017 ; Shen et al, 2019 ; Chen et al, 2021b ), each one in Iran ( Raeissadat et al, 2018 ) and Greece ( Malahias et al, 2018 ). In these included studies, CTS patients were treated with local autologous PRP injection in the experimental group and different types of conservative treatment in the control group.…”
Section: Resultsmentioning
confidence: 99%